Increasing the speed of automated ultrasonic inspection of as-built additive manufacturing components by the adoption of virtual source aperture. (August 2022) - Zimermann, Rastislav; Mohseni, Ehsan; Vithanage, Randika K.W.; Lines, David; Foster, Euan; Macleod, Charles N.; Gareth Pierce, Stephen; Marinelli, Gianrocco; Williams, Stewart; Ding, Jialuo
Graphical abstract: Highlights: Multi-layer adaptive ultrasound imaging using VSA for dry-coupled roller-probe inspection of AM components. Inspection of as-built dry-coupled Titanium WAAM components with artificial calibration reflectors. Increased data acquisition rate, increased speed of inspection and reduced data size while maintained sufficient SNR. Abstract: Wire + Arc Additive Manufacture (WAAM) is an economical manufacturing technique to build components. To maintain the commercial and technical benefits, inspection is desired at each layer of the build. New conformable phased array roller-probes offer the potential to inspect the as-built sample in-process or on completion. A challenge with such inspections is the refraction of the ultrasonic waves at multiple interfaces. The Synthetic Aperture Focusing Technique (SAFT) and Total Focusing Method (TFM), combined with Full Matrix Capture (FMC) acquisition enabled imaging through the as-built WAAM surface. However, single-element firings, associated with FMC are a limiting factor due to the lower energy at transmission, while the high number of firings and subsequent larger data size negatively affect inspection speed. This work introduces the concept of Virtual Source Aperture (VSA) for ultrasonic roller-probe inspection, through modelling of VSA on custom-designed calibration WAAM block. The concept is then demonstrated on a mock as-built WAAM sample inspection with reference defects. The results demonstrate that a markedly lower number of transmissions are required to match the performance of the FMC counterpart while increasing the energy levels. Moreover,  an almost 50% reduction in the data size enabled a doubling of the inspection speed.